A revised generic arrangement for the eagle ray family Myliobatidae, with definitions for the valid genera - White, William T. (Zootaxa, 2014)
The generic arrangement of the eagle rays (Family Myliobatidae) is revised and the genus Pteromylaeus Garman, 1913 is placed into the synonymy of Aetomylaeus Garman, 1908. Definitions are provided for the three valid genera, Aetobatus, Aetomylaeus and Myliobatis, and nomenclatural issues are discussed. Aetobatus differs from the latter two genera in having: a deeply notched nasal curtain, both jaws with a single row of chevron-shaped teeth, broadly rounded pectoral-fin free rear tips, pectoral fins separate from rostral lobe and joining head at level of eye. Aetomylaeus differs from the other two genera in having: pectoral fins separate from rostral lobe and joining head below level of eye, and stinging spine absent or present (usually not well developed when present). Myliobatis differs from the other two genera in having the pectoral fins joined to the rostral lobe by a subocular ridge. A list of valid species is provided, including a list of junior synonyms. Myliobatis australis Macleay, 1881 from southern Australia is placed into the synonymy of the previously considered endemic New Zealand species, M. tenuicaudatus Hector, 1877.